2015
DOI: 10.1589/jpts.27.3817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-intensity pulse irradiation with linear polarized near-infrared rays on muscle tone in patients with cerebrovascular disease: a randomized controlled trial

Abstract: [Purpose] This study evaluated effects of a high-intensity linear polarized near-infrared ray irradiation for mitigation of muscle hypertonia. [Subjects] The subjects were 20 patients with cerebrovascular disease. [Methods] Subjects were randomly allocated to an intervention or control group. The intervention group received irradiation of the triceps surae. Passive range of motion and passive resistive joint torque of ankle dorsiflexion were measured before and after the intervention in knee extended and flexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We previously reported the muscle tone-inhibitory effects of HI-LPNR irradiation 6 ) . Demura et al 15 ) reported that LPNR irradiation increased the range of motion in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported the muscle tone-inhibitory effects of HI-LPNR irradiation 6 ) . Demura et al 15 ) reported that LPNR irradiation increased the range of motion in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were the presence of surgical treatment or drug therapy for spasms (regardless of oral or injection), restriction of range of ankle joint motion on the paralytic side due to a reason other than hypertonia, and influence of pain or other reasons on measurement. This study was a developmental continuation of our previous study on the effects of HI-LPNR irradiation on hypertonia 6 ) and some subjects from the previous study were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation